Society’s Contribution to Silent Tendency of Sexually Assaulted Child as Reflected in Laurie Halse Anderson’s Speak - Resty Maudina Septiani; Eva Najma (Vivid: Journal of Language and Literature, 2017)
This research analyzes sexually-assaulted child’s silent tendency as depicted in Laurie Halse Anderson’s Speak. This social problem reflects one of social issues in America in 1999. I use sociology of literature theory from Alan Swingewood to analyze social issue in American society. This research uses descriptive qualitative method. I find that Laurie Halse Anderson depicts Melinda’s silent tendency is influenced by people around her. Sexually-assaulted child tends to not reporting the assault. It reflects sexual assault issue in America in 1999.